2017
DOI: 10.3892/etm.2017.5466
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16A regulates portal vein smooth muscle cell proliferation in portal hypertension

Abstract: Abstract. The aim of the present study was to elucidate the effect of transmembrane protein 16A (TMEM16A) on portal vein smooth muscle cell (PVSMC) proliferation associated with portal vein remodeling in portal hypertension (PHT). Sprague-Dawley rats were subjected to bile duct ligation to establish a rat model of liver cirrhosis and PHT. Sham-operated animals served as controls. At 8 weeks after bile duct ligation, the extent of liver fibrosis and the portal vein wall thickness were assessed using hematoxylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 41 publications
(44 reference statements)
3
26
0
4
Order By: Relevance
“…Primary antibodies. Goat polyclonal anti-Ano1 (catalog sc-69343, lot E2714), which recognizes epitope amino acids 825-875 of human Ano1, is validated by Sun et al (73) in pulmonary artery protein lysates and several labs in other tissues (74)(75)(76)(77)(78)(79). It shows a band of approximately 114 kDa in Western blot.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Primary antibodies. Goat polyclonal anti-Ano1 (catalog sc-69343, lot E2714), which recognizes epitope amino acids 825-875 of human Ano1, is validated by Sun et al (73) in pulmonary artery protein lysates and several labs in other tissues (74)(75)(76)(77)(78)(79). It shows a band of approximately 114 kDa in Western blot.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The TMEM protein superfamily comprises >310 different members, including membrane proteins, which are extensively expressed on cell and lysosomal membranes, and the endoplasmic reticulum, are strongly associated with membrane integrity, transport and signaling pathways (20). An increasing number of studies have investigated the TMEM superfamily and tumor-associated genes, particularly the oncogenes, TMEM16a (7,8), TMEM17a and TMEM17b (9) and the tumor suppressor gene TMEM100 (21,22). Certain TMEM genes have been reported to be involved in the development and metastasis of GC, such as TMEM16a (20).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have investigated the TMEM superfamily and tumor-associated genes, particularly the oncogenes, TMEM16a (7,8), TMEM17a and TMEM17b (9) and the tumor suppressor gene TMEM100 (21,22). Certain TMEM genes have been reported to be involved in the development and metastasis of GC, such as TMEM16a (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicated that activation of TMEM16A can limit the proliferation of pulmonary endothelial cells. Interestingly, X. Zeng et al () found that upregulation of TMEM16A contributes to portal vein smooth muscle cells proliferation in vitro. However, in vivo, the protein expression level of TMEM16A was significantly decreased in portal hypertension rat models (X. Zeng et al, ).…”
Section: Tmem16a and Hypertensionmentioning
confidence: 99%